Lung Tuberculosis with Multi Drug Resistant Risk in Tertiary Hospital in Middle Java - Ratna Wulan Febriyanti; Winarto Winarto; Mujahidah Mujahidah; Endang Sri Lestari; Purnomo Hadi; Vincentia Rizke Ciptaningtyas (Universitas Muhammadiyah Purwokerto, 2021)
World TB report from World Health Organization (WHO) in 2017 informed that Indonesia was second country with TB case. Multi Drug Resistance pulmonary infection’s case in Indonesia were 12.000. Kariadi hospital is one of tertiary hospital for pulmonary MDR-TB treatment but, there is no study about risk factor of it yet, so it needed to find risk factors of MDR-TB pulmonary infection in Kariadi hospital. Cross Sectional design using secondary data from Medical Record from January 1st - December 31, 2017 with result of Mycobacterium tuberculosis on GeneXpert sputum examination. Bivariate analysis with Chi square test and multivariate analysis was done by multiple logistic regression. The p value was considered significant if <0.05, all analyzes were 2-tailed. Totally 110 patients were obtained during periode, 55 samples for case and 55 samples for control. There were correlation between smoking habit OR = 3,1 (CI 95% 1,1-8,7), malnutrition OR = 2,9 (CI 95% 1,3-6,3), contact with patient with MDR pulmonary TB infection OR = 12,0 (CI 95% 1,5-97,3), past treatment OR = 81,7(CI 95% 23,4-285,2) and ≥6months past treatment OR = 94,5 (CI 95% 12,1-736,2. Risk factor that could influence together were contact with patient with MDR pulmonary TB infection OR = 34,5 (CI 95% 2,6-464,5), past treatment OR = 39,4 (CI 95% 8,3-186,3) and ≥ 6months past treatment OR = 12,4 (CI 95% 1,3-117,7). Risk factors for the incidence of pulmonary MDR TB infection are past contact with patient with MDR pulmonary TB infection, past treatment and ≥ 6months past treatment.